RESPON MASYARAKAT DALAM PELATIHAN BUDIDAYA DAN PEMBUATAN TEH TOGA - Nurcholis Nurcholis; Lilik Sumaryanti (Musamus University, 2021)
Survey of partner problems include (1) The potential of Sota village as a center for food crop agriculture, but it does not utilize the potential of home gardens by planting family medicinal plants. (2) Family medicinal plants are efficacious to increase body immunity, and are useful during the Covid-19 pandemic, but there has been no proper training. (3) The cultivation process by utilizing agricultural waste into organic fertilizer needs to be done. The methods used in solving this problem include training and mentoring from upstream to downstream, starting from making organic fertilizers, cultivating land, to processing toga products into toga tea. The results of the dedication showed that there was a positive response / very like reaching 93.33% of the 30 respondents for the process of making toga tea. This service program has an impact on the creativity and motivation of the community during the Covid-19 pandemic